Microenvironmental Management in Exhibition Spaces and Its Impact on the Physical Condition of the Medical Specimen Collection at the iMuseum IMERI, Faculty of Medicine, Universitas Indonesia - Aldila Amini Nasrul (Biokultur, 2026)
Medical specimens are a prominent collection of the IMERI FKUI iMuseum, which are used as a media for health and medical education for the community, making the specimens an important asset that must be preserved. Therefore, efforts to conserve the specimen collection are very important as part of preserving medical education media. One of the specimen conservation efforts is by managing the microenvironment of the medical specimen collection exhibition room at iMuseum. The lack of studies related to the management of the microenvironment of the exhibition room has become an obstacle in evaluating the factors causing damage to the collection. In addition, studies related to the management of the microenvironment of exhibition rooms for storing medical specimen collections in Indonesia are currently non-existent. Therefore, this study aims to determine the microenvironment of the exhibition room through environmental parameters, namely temperature, humidity, and light intensity, and their relationship with the physical condition of the specimen collection. Data collection was carried out by recording environmental parameters, including temperature, humidity, and light intensity, as well as observing the physical condition of the collection. The data were then analyzed descriptively. The results show that the average temperature and relative humidity of the specimen collection display room in 2023 and 2024 are within the ideal range, with an average temperature of 18-25°C and relative humidity of <60%. However, the average light intensity was in the high category, namely >50 lux. With these environmental conditions, the percentage of medical specimen collection maintenance activities in 2023–2024 for moldy specimens was 3.65%, discolored fluids were 17.65%, and reduced preservation fluids were 78.7%. These findings indicate that with the microenvironment in the exhibition room, medical specimens do not easily become moldy and preservation fluids do not undergo significant color changes. However, the findings regarding specimen fluid reduction due to evaporation remain high. Thus, microenvironment management in the medical specimen collection display room supports the maintenance of optimal microclimate conditions for preserving the medical specimen collection from fungal growth and preservation fluid discoloration.